Инновационные образовательные технологии в учебном процессе университета - Качеев, Д.А. (My University, 2016)
In article questions of use of innovative technologies in educational process of the higher school are considered. The analysis of modern methods and receptions innovative an education in higher education institutions is carried out.
Keywords: education; innovative methods; the higher school; health saving technology